Knowledge of Tuberculosis Treatment - A Survey Among Tuberculosis Patients in (DOTS) Program in Nepal - Bhatt, CP; Bhatt, AB; Shrestha, B (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2011)
Introduction: Tuberculosis (TB) has a long history. Its causative agent, Mycobacterium tuberculosis, may have killed more persons than any other microbial pathogen. Objective: To find out patients knowledge about tuberculosis treatment. Method: The study was carried out among the tuberculosis patients attended DOTS program in Nepal. Open ended self administered questionnaires based on the knowledge about Tuberculosis treatment were given to the survey population, literate group were asked to fill up the questionnaire and illiterate group were interviewed by a trained interviewer. Results: This prospective study included 300 diagnosed cases of pulmonary tuberculosis. The age of the respondents varied from 11-70 years. Males were outnumbered than females. Perception about the tuberculosis has been changed positively with the intervention of chemotherapy, 83% of the respondents knew that tuberculosis is a curable disease. Majority of the tuberculosis patients were found to be conscious about duration of treatment 8 months or more than 8 months (82%). Regarding the method of treatment, majority of them suggested consultation with doctor (75%). Knowledge for consequences of incomplete treatment, 25% of respondents answered disease may attack again and only 7.3% of the patients were aware that incomplete treatment will develop drug resistant tuberculosis. Conclusion: This survey showed that majority of patients knew that TB is a curable disease with regular treatment, duration of treatment and method of treatment. This will psychologically encourage them to abide by their treatment instructions. Patients’ knowledge about consequences of incomplete treatment was poor. This study suggests that more emphasis should be given on teaching patients about consequences of incomplete treatment. Key words: DOTS; Mycobacterium tuberculosis; Chemotherapy; Multi-drug resistant DOI: 10.3126/saarctb.v7i2.4399 SAARC J. TUBER. LUNG DIS. HIV/AIDS 2010 VII(2) 10-14